An Analysis of Grammatical Errors in Students' Proposals - Bahar, Pratiwi (Journal of ELT, Linguistics, and Literature, 2017)
This research aims to elaborate the kinds of grammatical errors and to disclose the factors that made the students do those kinds of grammatical errors. The data were collected from proposals written by the seventh semester students of English Department, Faculty of Letter, Hasanuddin University. These data were collected by using note-taking technique. The samples were 10 students’ proposals. The researcher to collect the data used random sampling technique. The writer used descriptive quantitative and qualitative methods in analyzing the data. The result of the data analyses shows that there are many kinds of grammatical errors, which students make in writing proposals, especially in Subject-Verb Agreement, Number Agreement, Reference, Word Order, Omitted Subject and Omitted Verb. The most frequent grammatical error that students make in writing proposals is Number Agreement. In addition, the factors that make students do some kinds of grammatical errors in writing proposals are overgeneralization, ignorance of rule restrictions, incomplete application of rules and false concept hypothesized.